The Implementation of Hypertension Exercise as an Independent Solution for the Elderly in Controlling Blood Pressure - S. Tauriana; Wimar Anugrah Romadhon; Ning Arti Wulandari (STIKes Patria Husada Blitar, 2025)
Hypertension is one of the leading causes of death in the world. Farmer groups are at risk of developing hypertension. Several contributing factors include exposure to pesticides, unhealthy lifestyles (such as lack of exercise, smoking, consumption of high-sodium foods, stress, and alcoholic beverages), and heavy work that can cause fatigue. Lifestyle modifications that are known to prevent hypertension are physical activities that are carried out regularly, such as hypertension gymnastics. The implementation of hypertension gymnastics has been carried out in the community in Pajarakan Village to help prevent hypertension using the field survey approach method and hypertension gymnastics training. A total of 26 participants participated in hypertension gymnastics which ended with the provision of hypertension gymnastics videos to representatives of the residents. Pre- and post-test screening was also carried out after 3 days of intervention to determine the decrease in blood pressure in the farmer group. The results obtained on the first, second and third days were 0.000 (<0.05), meaning that there was an effect of hypertension gymnastics on reducing blood pressure. The community is expected to be able to hold hypertension gymnastics independently and regularly.